Estructura de las prácticas docentes en probabilidad y estadística en las facultades de ingeniería en Bogotá, Colombia - Rocha Salamanca, Pedro (Revista Científica, 2011)
The present work is located inside the field of investigation named Statistical Education and exposes the development and analysis of an instrument of investigation that allows to describe some elements related to the educational practices of the teachers of probability and statistics in the powers of engineering in Bogota - Colombia.